A UV-resistant layered silicate functional masterbatch and its preparation method and application
By pickling and purification of high mesh layered silicates and modifying ultraviolet absorber treatment, functional masterbatches of ultraviolet aging resistance were prepared, which solved the problem of insufficient UV aging resistance in biodegradable plastic films. The material's ultraviolet aging resistance and rigidity are improved.
Patent Information
- Application Number
- CN202211604552.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-12-13
- Publication Date
- 2025-02-11
- Estimated Expiration
- 2042-12-13
AI Technical Summary
The existing layered silicate masterbatch lacks UV aging resistance in biodegradable plastic films and may accelerate the photooxygen aging reaction of biodegradable polyester.
By pickling and purifying the high mesh layered silicate and co-treated with the modified ultraviolet absorber, a high-strength, highly dispersed layered silicate functional masterbatch is prepared. The masterbatch obtains the ultraviolet absorber-modified layered silicate powder in situ by surface modification, and combines the biodegradable resin to form an UV-resistant biodegradable composite.
It has achieved the improvement of UV aging resistance and rigidity of biodegradable materials, has long-term anti-UV aging effect, and effectively inhibits the migration of small molecule UV absorbers, improving the anti-extraction ability.
Smart Images

Figure CN115785628B_ABST
Abstract
Description
Technical field:
[0001] The invention relates to the technical field of plastic additives, and in particular to a UV-resistant aging-resistant layered silicate functional masterbatch and a preparation method and application thereof. Background technology:
[0002] Layered silicate filler powder, as a low-cost, low-coloring inorganic layered reinforcing functional filler, plays an important role in the field of plastic processing. It can give plastics higher rigidity, creep resistance and better barrier properties at both room temperature and high temperature. When used, in order to avoid dust pollution, improve processability and metering reliability, layered silicate powder is usually modified to make masterbatch. However, in the existing technology, layered silicate masterbatch has no obvious effect on the UV aging resistance of biodegradable mulch, and may accelerate the photo-oxidation aging reaction of biodegradable polyester due to its own impurities.
[0003] As an inorganic filler with a relatively large mass proportion in plastics, the UV aging resistance of existing biodegradable talc masterbatch needs to be further enhanced. The use of intercalation structure can inhibit the precipitation of small molecule additives, but the intercalation assembly has high requirements for the preparation process, which is not conducive to industrial utilization. Patent CN113416324A discloses a biodegradable talc masterbatch and its preparation process, aiming to solve the problems that the existing talc masterbatch does not have biodegradability and its improvement of the mechanical properties of degradable plastic products needs to be further strengthened. Patent CN105801906A discloses a migration-resistant calcium-based intercalation structure polyolefin antioxidant and its preparation method. None of the above inventions have achieved the improvement of the UV aging resistance of fully biodegradable agricultural mulch, nor have they significantly reduced the thickness of the fully biodegradable mulch on the basis of enhanced weather resistance. At present, there is no highly weather-resistant and transparent relatively low-priced fully biodegradable mulch that has been commercialized. Summary of the invention:
[0004] The present invention solves the problems existing in the prior art and provides a high-strength, high-dispersion, environmentally friendly UV-resistant layered silicate functional masterbatch and a preparation method and application thereof. The present invention improves the rigidity of the material by using high-mesh layered silicate and cooperates with a modified UV absorber to shield ultraviolet rays, so that the biodegradable material can have both good rigidity and UV-resistant properties.
[0005] The purpose of the present invention is to provide a UV-resistant aging layered silicate functional masterbatch, which comprises the following components by weight: 50 to 90 parts of a biodegradable resin and 10 to 50 parts of a high-mesh layered silicate modified by an ultraviolet absorber. The high-mesh layered silicate modified by an ultraviolet absorber is prepared by the following steps:
[0006] (1) washing and purifying the high-mesh layered silicate with a dilute nitric acid solution, washing with water until neutral, and drying to obtain a purified high-mesh layered silicate;
[0007] (2) The ultraviolet absorber is dissolved in an organic solvent, and a purified high-mesh layered silicate is added, heated to boiling, and refluxed for 2-8 hours. The obtained reaction product is filtered, dried, crushed, and then paraffin is added. The mixture is stirred continuously for encapsulation to obtain a high-mesh layered silicate modified with an ultraviolet absorber.
[0008] The present invention obtains ultraviolet absorber-modified layered silicate powder in situ by simple surface modification of ultraviolet absorbing groups, and forms an anti-ultraviolet biodegradable composite material with ultraviolet absorbing function with ultraviolet absorber-modified layered silicate filler and biodegradable resin. The ultraviolet aging-resistant layered silicate functional masterbatch synthesized by the present invention has a long-term anti-ultraviolet aging effect, can improve the external migration of small molecule UV absorbers, is a highly efficient, multifunctional, environmentally friendly biodegradable plastic additive, and has important application prospects in the plastics industry.
[0009] Preferably, the biodegradable polyester is selected from one or two of polybutylene adipate / terephthalate (PBAT), polymethyl ethylene carbonate (PPC) and polylactic acid (PLA).
[0010] Preferably, the layered silicate is selected from one of talc, mica, pyrophyllite and kaolin, and the high-mesh layered silicate is above 3000 mesh.
[0011] Preferably, the ultraviolet absorber is selected from one or two of 4,4-dihydroxybenzophenone, 2-cyano-3,3-diphenylacrylate, cyanoacrylate, 2-cyano-3,3-diphenylacrylate ethyl ester, N-(ethoxycarbonylphenyl)-N'-methyl-N'-phenyl methyl ether and 2-hydroxy-4-methoxybenzophenone.
[0012] Preferably, the mass ratio of the ultraviolet absorber to the high-mesh layered silicate in step (2) is 1 / 100 to 10 / 100, and the mass ratio of paraffin to the high-mesh layered silicate is 1 / 100 to 10 / 100. More preferably, the reflux reaction is carried out under boiling conditions for 6-8 hours.
[0013] Preferably, the mass ratio of the ultraviolet absorber-modified high-mesh layered silicate to the biodegradable polyester is 1:1.
[0014] Preferably, the solvent in step (2) is selected from one or two of ethanol, dichloromethane and chloroform.
[0015] The present invention also provides a method for preparing the above-mentioned UV-resistant aging-resistant layered silicate functional masterbatch, comprising the following steps:
[0016] (1) washing and purifying the high-mesh layered silicate with a dilute nitric acid solution, washing with water until neutral, and drying to obtain a purified high-mesh layered silicate;
[0017] (2) The ultraviolet absorber is dissolved in an organic solvent, and a purified high-mesh layered silicate is added, heated to boiling, and refluxed for 2-8 hours. The obtained reaction product is filtered, dried, crushed, and then paraffin is added, and the stirring is continued for encapsulation to obtain a high-mesh layered silicate modified with an ultraviolet absorber;
[0018] (3) The high-mesh layered silicate modified by the ultraviolet absorber is mixed with the biodegradable resin, and granulated by twin-screw extrusion to obtain the ultraviolet aging-resistant layered silicate functional masterbatch.
[0019] Preferably, the temperature of the twin-screw extrusion granulation in step (3) is 130°C.
[0020] The present invention also protects the application of the UV-resistant layered silicate functional masterbatch in inorganic weather-resistant masterbatch or biodegradable agricultural film.
[0021] Compared with the prior art, the present invention has the following advantages:
[0022] (1) The UV-resistant layered silicate functional masterbatch proposed in the present invention performs acid washing and purification on the layered silicate filler, which can increase the reactive groups on the surface of the inorganic layered silicate filler, inhibit the reverse promotion of the layered silicate filler on the photoaging of the biodegradable resin, and endow the plastic filler with excellent UV-resistant properties;
[0023] (2) The UV-resistant layered silicate functional masterbatch proposed by the present invention uses a reactive UV absorber instead of a coupling agent to impart UV absorption to the layered silicate, while improving the rigidity and UV-resistant effect of the biodegradable material, thus having a dual-functional enhancement effect;
[0024] (3) The preparation process of the UV-resistant layered silicate functional masterbatch provided by the present invention is simple, the process is simple, the raw materials are abundant, and it is easy to mass produce, which is beneficial to environmental protection, cost reduction and industrial promotion. Description of the drawings:
[0025] Figure 1 This is a SEM photo of the UV-resistant layered silicate functional masterbatch 1 in Example 1;
[0026] Figure 2 This is a comparison chart of the UV absorber precipitation amount of the PBAT films prepared in Application Examples 1 and 4 immersed in ethanol for 24 hours. Specific implementation method:
[0027] The following examples are provided to further illustrate the present invention, rather than to limit the present invention.
[0028] Unless otherwise defined, all professional terms used hereinafter have the same meaning as those generally understood by those skilled in the art. The professional terms used herein are only for the purpose of describing specific embodiments and are not intended to limit the scope of protection of the present invention. Unless otherwise specified, the experimental materials and reagents herein are conventional commercial products in the art.
[0029] The dilute nitric acid solution used in the purification of layered silicate in the following examples is a nitric acid solution with a mass fraction of 5%-10%. The mass concentration of the ultraviolet absorber dissolved in the organic solvent is 0.01-0.05 g / mL.
[0030] Example 1
[0031] A method for preparing a UV-resistant layered silicate functional masterbatch comprises the following steps:
[0032] (1) washing and purifying 3000 mesh talc with dilute nitric acid solution, ultrasonicating for 20 minutes, washing with water until neutral, and drying to obtain purified talc;
[0033] (2) 0.01 kg of cyanoacrylate was dissolved in 1 liter of chloroform, 1 kg of purified talc was added, the mixture was heated to boiling, and refluxed for 6 hours. The obtained reaction product was filtered, dried at 80° C. for 12 hours, crushed in a powder mill for 5 minutes, 0.02 kg of paraffin was added, and the crushing was continued for 1 minute to obtain a talc filler modified with a UV absorber;
[0034] (3) The talc filler modified by the ultraviolet absorber is mixed with the polybutylene adipate / terephthalate resin in a mass ratio of 1:1, and granulated by twin-screw extrusion at 130° C. to obtain the ultraviolet aging resistant layered silicate functional masterbatch 1.
[0035] The obtained UV-resistant layered silicate functional masterbatch 1 was characterized, as shown in FIG. Figure 1 As shown, from Figure 1 It can be seen that the UV-resistant layered silicate functional masterbatch 1 is a lamellar structure with a diameter of about 5 μm.
[0036] Example 2
[0037] A method for preparing a UV-resistant layered silicate functional masterbatch comprises the following steps:
[0038] (1) 3000 mesh muscovite was cleaned and purified with dilute nitric acid solution, ultrasonicated for 20 minutes, washed with water until neutral, and dried to obtain purified mica powder;
[0039] (2) 0.01 kg of cyanoacrylate was dissolved in 1 liter of dichloromethane, and 1 kg of purified mica powder was added. The mixture was refluxed under boiling conditions for 6 hours. The obtained reaction product was filtered, dried at 80° C. for 12 hours, crushed in a powder grinder for 5 minutes, and 0.02 kg of paraffin was added. The mixture was crushed for another minute to obtain a mica powder filler modified with an ultraviolet absorber.
[0040] (3) The ultraviolet absorber-modified mica powder filler and polybutylene adipate / terephthalate resin were mixed in a mass ratio of 1:1, and granulated by twin-screw extrusion at 130° C. to obtain ultraviolet aging-resistant layered silicate functional masterbatch 2.
[0041] Example 3
[0042] A method for preparing a UV-resistant layered silicate functional masterbatch comprises the following steps:
[0043] (1) washing and purifying talc powder of 10000 mesh with dilute nitric acid solution, ultrasonicating for 20 minutes, washing with water until neutral, and drying to obtain purified talc powder;
[0044] (2) 0.01 kg of cyanoacrylate was dissolved in 1 liter of chloroform solvent, 1 kg of purified talc was added, and the mixture was refluxed under boiling conditions for 8 hours. The obtained reaction product was filtered, dried at 80° C. for 12 hours, crushed in a powder grinder for 5 minutes, 0.05 kg of paraffin was added, and the mixture was crushed for another minute to obtain a talc filler modified with an ultraviolet absorber;
[0045] (3) The talc filler modified with the ultraviolet absorption group is mixed with the polybutylene adipate / terephthalate resin in a mass ratio of 1:1, and granulated by twin-screw extrusion at 130° C. to obtain the ultraviolet aging-resistant layered silicate functional masterbatch 3.
[0046] Example 4
[0047] A method for preparing a UV-resistant layered silicate functional masterbatch comprises the following steps:
[0048] (1) washing and purifying 3000 mesh talc with dilute nitric acid solution, ultrasonicating for 20 minutes, washing with water until neutral, and drying to obtain purified talc;
[0049] (2) 0.01 kg of cyanoacrylate was dissolved in 1 liter of chloroform, 1 kg of purified talc was added, the mixture was heated to boiling, and refluxed for 6 hours. The obtained reaction product was filtered, dried at 80° C. for 12 hours, crushed in a powder mill for 5 minutes, 0.01 kg of paraffin was added, and the crushing was continued for 1 minute to obtain a talc filler modified with a UV absorber;
[0050] (3) The talc filler modified with the ultraviolet absorber is mixed with the polybutylene adipate / terephthalate resin in a mass ratio of 1:5, and granulated by twin-screw extrusion at 130° C. to obtain the ultraviolet aging-resistant layered silicate functional masterbatch 4.
[0051] Example 5
[0052] A method for preparing a UV-resistant layered silicate functional masterbatch comprises the following steps:
[0053] (1) washing and purifying 3000 mesh talc with dilute nitric acid solution, ultrasonicating for 20 minutes, washing with water until neutral, and drying to obtain purified talc;
[0054] (2) 0.11 kg of cyanoacrylate was dissolved in 1 liter of chloroform, 1 kg of purified talc was added, the mixture was heated to boiling, and refluxed for 6 hours. The obtained reaction product was filtered, dried at 80° C. for 12 hours, crushed in a powder mill for 5 minutes, 0.1 kg of paraffin was added, and the crushing was continued for 1 minute to obtain a talc filler modified with a UV absorber;
[0055] (3) The talc filler modified by the ultraviolet absorber is mixed with the polybutylene adipate / terephthalate resin in a mass ratio of 1:9, and granulated by twin-screw extrusion at 130° C. to obtain the ultraviolet aging resistant layered silicate functional masterbatch 5.
[0056] Comparative Example 1
[0057] A method for preparing a layered silicate functional masterbatch comprises the following steps:
[0058] (1) 3000 mesh talc was cleaned and purified with dilute nitric acid solution, ultrasonicated for 20 minutes, washed with water until neutral, and dried at 80° C. for 12 hours;
[0059] (2) 1 kg of purified talc was mixed with 0.01 kg of cyanoacrylate and 0.02 kg of paraffin, and the mixture was crushed and stirred for 5 minutes using a powder grinder to obtain a talc filler modified with an ultraviolet absorber;
[0060] (2) The talc filler modified with the ultraviolet absorber was mixed with the polybutylene adipate / terephthalate resin in a mass ratio of 1:1, and granulated by twin-screw extrusion at 130° C. to obtain the layered silicate functional masterbatch 6.
[0061] Application Examples 1-6
[0062] The functional masterbatch obtained in Examples 1-5 and Comparative Example 1 was mixed with poly(butylene adipate / terephthalate) resin in equal mass, and film was blown at 130°C using a film blowing machine to obtain a biodegradable mulch film with a thickness of 15 μm, which were respectively recorded as Application Example 1, Application Example 2, Application Example 3, Application Example 4, Application Example 5 and Application Example 6. Application Examples 1-6 were cut into strips with a width of 1 cm and a length of 10 cm along the film blowing direction (longitudinal direction) for ultraviolet aging performance test and precipitation experiment. Accelerated aging experiments were carried out in the laboratory according to GB / T 16422.3-2014 / ISO4892-3:2006 standard, with a temperature of 60°C and an irradiance of 0.89 W·m -1 ·nm -1 After 72 hours, samples were taken to test the tensile mechanical properties. The tensile mechanical properties test was carried out according to GB / T 1040.2 standard, and the test speed was 500 mm min -1 (The test results are shown in Table 1). The sample strips cut from Application Examples 1 and 6 were immersed in anhydrous ethanol at a mass ratio of 1:100, and magnetically stirred for 24 hours. The absorbance of the upper solution was tested to compare the migration resistance of the UV absorbing additive (e.g. Figure 2 shown).
[0063] Table 1 Comparison of mechanical parameters of blown films before and after aging between examples and comparative examples
[0064]
[0065] from Figure 2 It can be seen that after immersion for 24 hours, more UV absorbers are precipitated by the blending method used in Application Example 4. The comparison proves that the modification method used in the present invention can effectively inhibit the external migration of small molecule UV absorbers and improve the anti-extraction ability.
[0066] As can be seen from Table 1, Application Examples 1-3 have a higher initial tensile strength, and the order from large to small is Example 3> Example 2> Example 1> Example 4> Example 5> Comparative Example 1. This is because the modification method of the present invention can effectively improve the dispersibility of the layered silicate material in the polymer matrix, and has a good reinforcing effect on the polymer, and the reinforcing effect of talcum powder is better when added with the same mass ratio. After aging for 72 hours, the elongation at break retention rates are from large to small as Example 3> Example 1> Example 5> Example 2> Example 4> Comparative Example 1. This is because the talcum powder used in Example 3 has a higher specific surface area, and the content of ultraviolet absorber encapsulated on its surface is higher, and the anti-ultraviolet aging protection effect on the polymer matrix is stronger; after aging, Example 5 has a higher elongation at break retention rate than Example 4. It can be seen from the comparison that under the premise of ensuring the encapsulation rate, reducing the content of layered silicate filler within a range can still ensure the anti-ultraviolet aging protection ability of the masterbatch for biodegradable resin.
[0067] In summary, the UV-resistant layered silicate composite material of the present invention replaces the coupling agent with a reactive UV absorber to impart UV absorption to the layered silicate, while improving the rigidity and UV-resistant effect of the biodegradable material, thus having a dual-function enhancement effect.
[0068] The description of the above embodiments is only used to help understand the technical solution and core ideas of the present invention. It should be pointed out that for technicians in this technical field, several improvements and modifications can be made to the present invention without departing from the principles of the present invention. These improvements and modifications also fall within the scope of protection of the claims of the present invention.
Claims
1. A UV-resistant layered silicate functional masterbatch, characterized in that: The composition comprises the following components by weight: 50-90 parts of biodegradable resin and 10-50 parts of high-mesh layered silicate modified by ultraviolet absorber, wherein the high-mesh layered silicate modified by ultraviolet absorber is prepared by the following steps: (1) washing and purifying the high-mesh layered silicate with a dilute nitric acid solution, washing with water until neutral, and drying to obtain a purified high-mesh layered silicate, wherein the mesh number of the high-mesh layered silicate is greater than 3000 mesh; (2) The ultraviolet absorber is dissolved in an organic solvent, and a purified high-mesh layered silicate is added thereto. The reaction is refluxed for 2-8 hours under boiling conditions. The obtained reaction product is filtered, dried, crushed, and then paraffin is added thereto. The mixture is stirred continuously for encapsulation to obtain a high-mesh layered silicate modified with an ultraviolet absorber. The mass ratio of the ultraviolet absorber to the high-mesh layered silicate is 1 / 100-10 / 100, the mass ratio of the paraffin to the high-mesh layered silicate is 1 / 100-10 / 100, and the ultraviolet absorber is cyanoacrylate.
2. The UV-resistant layered silicate functional masterbatch according to claim 1, characterized in that: The biodegradable resin is selected from one or two of polybutylene adipate / terephthalate, polymethyl ethylene carbonate and polylactic acid.
3. The UV-resistant layered silicate functional masterbatch according to claim 1, characterized in that: The layered silicate is selected from one of talc, mica, pyrophyllite and kaolin.
4. The UV-resistant layered silicate functional masterbatch according to any one of claims 1 to 3, characterized in that: The mass ratio of the ultraviolet absorber-modified high-mesh layered silicate to the biodegradable resin is 1:
1.
5. The UV-resistant layered silicate functional masterbatch according to claim 1, characterized in that: The solvent in step (2) is selected from one or two of ethanol, dichloromethane and chloroform.
6. The method for preparing the UV-resistant layered silicate functional masterbatch according to any one of claims 1 to 5, characterized in that: The following steps are involved: (1) washing and purifying the high-mesh layered silicate with a dilute nitric acid solution, washing with water until neutral, and drying to obtain a purified high-mesh layered silicate; (2) The ultraviolet absorber is dissolved in an organic solvent, and a purified high-mesh layered silicate is added, and the reaction is refluxed for 2-8 hours under boiling conditions. The obtained reaction product is filtered, dried, crushed, and then paraffin is added, and the stirring is continued for encapsulation to obtain a high-mesh layered silicate modified with an ultraviolet absorber; (3) The high-mesh layered silicate modified with an ultraviolet absorber is mixed with a biodegradable resin and granulated by twin-screw extrusion to obtain a layered silicate functional masterbatch resistant to ultraviolet aging.
7. The preparation method according to claim 6, characterized in that: The temperature of the twin-screw extrusion granulation in step (3) is 130°C.
8. Use of the UV-resistant layered silicate functional masterbatch according to any one of claims 1 to 5 in inorganic weather-resistant masterbatch or biodegradable agricultural film.
Citation Information
Patent Citations
Migration-resisting calcium-based intercalated structure polyolefin antioxidant and preparation method thereof
CN105801906A
Biodegradable talcum powder master batch and preparation process thereof
CN113416324A
Plastic additive with anti-ultraviolet ageing and moisturizing property and preparation method and application thereof
CN108219392A